Association between DNA methylation and ADHD symptoms from birth to school age: a prospective meta-analysis - Neumann, Alexander; Walton, Esther; Alemany, Silvia; Cecil, Charlotte; González, Juan Ramon; Jima, Dereje D.; Lahti, Jari; Tuominen, Samuli T.; Barker, Edward D.; Binder, Elisabeth; Caramaschi, Doretta; Carracedo, Ángel; et al. (Translational psychiatry, 2020)
Attention-deficit and hyperactivity disorder (ADHD) is a common childhood disorder with a substantial genetic component. However, the extent to which epigenetic mechanisms play a role in the etiology of the disorder is unknown. We performed epigenome-wide association studies (EWAS) within the Pregnancy And Childhood Epigenetics (PACE) Consortium to identify DNA methylation sites associated with ADHD symptoms at two methylation assessment periods: birth and school age. We examined associations of both DNA methylation in cord blood with repeatedly assessed ADHD symptoms (age 4–15 years) in 2477 children from 5 cohorts and of DNA methylation at school age with concurrent ADHD symptoms (age 7–11 years) in 2374 children from 9 cohorts, with 3 cohorts participating at both timepoints. CpGs identified with nominal significance ( p < 0.05) in either of the EWAS were correlated between timepoints ( ρ = 0.30), suggesting overlap in associations; however, top signals were very different. At birth, we identified nine CpGs that predicted later ADHD symptoms ( p < 1 × 10 –7 ), including ERC2 and CREB5 . Peripheral blood DNA methylation at one of these CpGs (cg01271805 in the promoter region of ERC2 , which regulates neurotransmitter release) was previously associated with brain methylation. Another (cg25520701) lies within the gene body of CREB5 , which previously was associated with neurite outgrowth and an ADHD diagnosis. In contrast, at school age, no CpGs were associated with ADHD with p < 1 × 10 −7 . In conclusion, we found evidence in this study that DNA methylation at birth is associated with ADHD. Future studies are needed to confirm the utility of methylation variation as biomarker and its involvement in causal pathways.